Learning Orthographic Cognates and Non‐Cognates in the Classroom: Does Awareness of Cross‐Linguistic Similarity Matter?. Issue 3 (22nd February 2020) - Otwinowska, Agnieszka; Foryś‐Nogala, Małgorzata; Kobosko, Weronika; Szewczyk, Jakub
Abstract: Some second language (L2) acquisition researchers have suggested that learners should be made aware of cross‐linguistic similarity for them to benefit from cognateness. To test this assumption, we ran two longitudinal classroom quasi‐experiments with Polish learners of English. We chose 30 Polish‐English cognates, 30 false cognates, and 30 non‐cognates matched on L2 frequency and concreteness and embedded them in exercises typical of English language teaching textbooks. Participants learned the words with their teachers in their classes at school. We manipulated the experimental group's awareness of orthographic cross‐linguistic similarity in awareness‐raising workshops. The results revealed that the participants had a higher chance of knowing cognates than other word types before the study. However, they acquired cognates embedded in exercises at the same rate as other word types. Also, the awareness‐raising manipulation, regardless of its intensity, had no additional effect on their acquisition of cognates and false cognates, indicating that awareness of cognateness did not boost learning cognates. Abstract :